Varstvo interesov delavcev v postopkih privatizacije družb v državni lasti - Hojnik, Janja (Delavci in delodajalci, 2015)
The author argues that the state aid rules are not the only rules that are binding on the performance of the privatisation process. Privatisation concerns the rules on state aid, as well as rules on takeovers, the free competition and the workers' participation, which represents not only the category of Slovenian constitutional law, but also a fundamental principle of EU law. All of them must also be taken into account.
Keywords: državna lastnina; državna pomoč; gospodarske družbe; pravice; privatizacija; zaposleni